The unequal effects of resettlement in coastal regions - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel explains how climate-related resettlement, often presented as a solution to coastal hazards, can unintentionally increase vulnerability if social differences are ignored. Using the case of fishing communities resettled inland in Saint Louis, Senegal, it walks through what is known as managed resettlement and asks a critical question: what happens to people’s lives after they move? The research shows that resettlement can become maladaptation, deepening poverty, isolation, and insecurity for some groups. Women lost access to fish markets and livelihoods, while young unmarried people became more socially and economically disconnected. The carousel highlights that resettlement did not create these inequalities but magnified existing ones, and argues that effective climate adaptation must be planned with communities, accounting for livelihoods, gender roles, and social hierarchies, not just physical safety